Correlation Between Duration of Hypertension and Level of Adherence to Hypertensive - Rizqi Suryani Putri; Henry Mulyono (Syntax Literate, 2022)
Hypertension is a major cause of premature death worldwide.16,95% citizen were diagnosed with hypertension and Balowerti area had the highest cases in Kediri City. The adherence to antihypertensive medications is a key component to control blood pressure levels. Poor adherence to these medications leads to the development of hypertensive complications and increase risk of cardiovascular events which in turn reduces the ultimate clinical outcome. Duration of hypertension status is one of the factors that affect the level of adherence. Previously, there were several similar studies with varying results. This study is needed to give early intervention to reduce complications and patient mortality. Aim: This study aims to find the correlation between the duration of hypertension and the level of adherence to antihypertensive medication in Balowerti Public Health Center Kediri. A cross-sectional study was carried out to 106 patients with hypertension in the work area of Balowerti Public Health Center, Kediri, East Java, Indonesia using accidental sampling. Morisky Medication Adherence Scale (MMAS-8) questionnaire was used to measure the level of adherence to antihypertensive medication. Data were analysed with the Spearman correlation test. Results: This study showed a significant correlation between the duration of hypertension and the level of adherence to antihypertensive medication (p =0.011, p < 0,05). Duration of hypertension was significantly correlated with the level of adherence to antihypertensive medication. The longer duration of hypertension, the lower level of adherence to antihypertensive medication